Luther E. Martin, 1937. - Unknown (Forsyth County Public Library, 1937)
Source: "North Carolina Municipal News, September, 1937."
Luther E. Martin, 1937. Mr. Martin was an Alderman. He was also associated with Martin Advertising Service and Martin Textile Device Company.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth